2010
DOI: 10.1017/s0954422410000016
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and shift work: chronobiological aspects

Abstract: The present review has the objective of summarising chronobiological aspects of shift work and obesity. There was a systematic search in PubMed databases, using the following descriptors: shift work; obesity; biological clock. Shift work is extremely frequent in several services and industries, in order to systematise the needs for flexibility of the workforce, necessary to optimise productivity and business competitiveness. In developing countries, this population represents a considerable contingent workforc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
333
4
59

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 409 publications
(402 citation statements)
references
References 95 publications
6
333
4
59
Order By: Relevance
“…The effect of shift work on body weight has been investigated in previous studies, several of which demonstrated a significant tendency to become overweight [6,27,28]. In contrast, some studies failed to show such associations [15,29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of shift work on body weight has been investigated in previous studies, several of which demonstrated a significant tendency to become overweight [6,27,28]. In contrast, some studies failed to show such associations [15,29].…”
Section: Discussionmentioning
confidence: 99%
“…Weight gain in shift workers has been explained by several mechanisms, such as higher calorie intake, changes in dietary habits (such as eating fewer meals and more snacks) and the circadian distribution of food intake [5,6], as well as lower physical exercise and changes in sleeping habits [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Pracę zmianową uznaje się za czynnik predykcyjny rozwoju otyłości, cukrzycy typu 2 i zespołu metabolicznego. [25][26][27] U osób narażonych na zmienność rytmu dobowego wykazano supresję produkcji leptyny, uznawanej za hormon sytości, oraz wzrost stężenia insuliny i glukozy w krwiobiegu. U osób chorujących na cukrzycę ograniczenie snu prowadzi do pogorszenia kontroli choroby, 28 czego powodem może być zubożenie jadłospisów pacjentów oraz spożywanie przez nich mniejszej ilości różno-rodnych pokarmów o niskim stopniu przetworzenia.…”
Section: Rola Melatoniny W Ustrojuunclassified
“…In addition, the main cause of insomnia in shift workers is changes in the circadian rhythm (13,14). Antunes showed that 62% of people suffer from sleep disorders and insomnia is the most common complaint of shift workers (15). Dorrian et al concluded that shift work causes increases the body weight and this causes an increase in BMI and waist circumference.…”
Section: Introductionmentioning
confidence: 99%